PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA SEPEDA MOTOR MATIC HONDA BEAT: Studi Kasus Pada Konsumen Ciledug - Zikril Hakim, - (2019)
This research is a quantitative research that aims to determine the effect of brand image, product quality, and promotion on buying decision. The population in this study were Honda Beat matic motorcycle consumers in Ciledug. The sample size was taken as many as 70 respondents, with a non probability sampling method and focused on accidental sampling. The data collected through the distribution of questionnaires. The analysis technique is using PLS (Partial Least Square) analysis with SmartPLS3.0 software. The results of this study indicates that (1) Brand image has a positive and significant influence on buying decision. (2) Product quality has a positive and significant influence on buying decision. (3) Promotion has no influence and is not significant on buying decision. Based on the three independent variables which is brand image, product quality, and promotion the one that has most contribution is the product quality variable.